Genetic polymorphisms of CYP 3A4 & CYP2C8 in healthy volunteers title of project administered with repaglinide - Hua, Gan Siew (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Repaglinide is a novel prandial glucose regulator (PG R) for the treatment of type 2 diabetes mellitus. Repaglinide is mainly metabolised in the liver by CYP3A4 and CYP2C8 enzymes. The objective of the present study is to investigate the effects of the CYP3A4 and CYP2CB genotypes on the pharmacokinetics of repaglinide in 121 healthy Malaysian subjects. The study protocol was approved by our local Research and Ethics Committee, School of Medical Sciences, Universiti Sains Malaysia. Initially, a new HPLC method using a simple liquid-liquid extraction for the determination of repaglinide in human serum was developed and later validated. Then, PCR methods were optimized to detect CYP3A4 and CYP2CB genetic polymorphisms among healthy Malaysian subjects. Each subject received 4 mg of oral repaglinide. Six blood samples per individual were taken (0 min, 30 min, 60 min, 120 min, 180 min and 240 min) for repaglinide's serum concentration determination by using HPLC. NPAG was then ' used to determine population pharmacokinetic parameter values of repaglinide. The developed HPLC method was selective and calibration curves of repaglinide were found to be linear in the concentration range of 20-200 ng/ml. The limits of detection (LOD) and quantification (LOQ) were 10 ng/ml and 20 ng/ml, respectively. The inter-day precision was from 5.21%, to 11.84°/o while the intra-day precision ranged from 3.90%, to 6.67°/o. The inter-day accuracy ranged between 89.95% and 105.75%> with the intra-day accuracy ranging from 92.37°/o to 104.66%. No mutations were detected for the CYP3A4*4 and CYP3A4*5 alleles. The frequency of the CYP3A4*18 allele was 2.07o/o. All five subjects with CYP3A4*18 mutations were found to be heterozygous. For CYP2C8, the allele frequency for both CYP2C8*2 and *3 was 0.4°/o while the allele frequency for CYP2C8*5 was 4.13o/o. All subjects with mutations were found to be heterozygous. No mutation was detected for the CYP2C8*4 allele. CYP2C8 and CYP3A4 genotypes were not significantly associated with changes in the blood glucose lowering effect of repaglinide. On the other hand, the CYP3A4 genotype significantly influenced repaglinide's pharmacokinetics where the mean elimination rate constant (kel) was 34% lower (p = 0.04) and the mean half-life (t112) was 133°/o longer (p = 0.04) i.n subjects having the CYP3A4*11*18 genotype compared to those having the CYP3A4*11*1 genotype. In conclusion, CYP3A4 activity plays an important role in influencing ' repaglinide's pharmacokinetics. Therefore, subjects having CYP3A4*11*18 may need to receive lower doses of repaglinide.